Diffraction around a Semi-Parabolic Canyon in an Elastic Half-Space by Out-of-Plane SH-Waves, II: Rocking and Resultant Rotations. Issue 1 (2nd January 2018) - Lee, Vincent W.; Lin, Chi-Hsin; Teng, Liping
Abstract : This paper is the second of the two papers, discussing the rocking and resultant component of rotations, with the torsional components of motions presented earlier in the first paper for the case of out-of-plane SH waves excitation on a semi-parabolic canyon. The rotational motions are gaining importance in recent years in the field of strong-motion seismology and earthquake engineering. Many previous papers on out-of-plane SH waves excitation presented the associated torsion rotational motions, when in fact there is also a rocking rotational component of motions. Both the rocking and torsion rotational motions, in as much as the translational motions, had shown to play an important role in structural responses, even though rotations are not incorporated into building design codes at present. Studying the rotational motions can thus help to a better understanding of the behavior of surface topographies that are in the vicinity of structures in the event of seismic excitation. This paper included, besides the additional rocking motions, also the resultant rotational motions combining torsion and rocking.